ORGANIZATION OF WORK AND CONCEPTUAL MODEL OF THE STUDY OF PSYCHOLOGICAL COMPONENTS OF UNIVERSITY IMAGE - Chernega, Natalia (PSYCHOLOGICAL JOURNAL, 2017)
In the article «Organization of the conceptual model and research the psychological components of the image of the University» an analysis of scientific approaches, organization of work, research tools psychodiagnostic defined components that affect the formation of the image of the university, defining the content of the conceptual model, grounded methods. This study uses general scientific principles: the principle of system approach to understanding personality principle of determinism and development, unity and consciousness of the individual, methodological principles of research. The analysis of scientific sources theoretical and methodological approaches of psychological determinants of image formation educational institutions found that a significant number of identifiable components indicate the possibility and the need to clarify the internal and external factors that contribute to image formation, and on the other side - indicate need for an integrated approach to research on determinants psychodiagnostic image of higher education. Problems related to psychological diagnosis image of higher education organization in modern Ukrainian and foreign scientific literature considered insufficiently because scientific research is a practical objective study methods and develop a conceptual model study forming the image of the university. Therefore, the analysis of scientific sources of theoretical and methodological approaches developed and the content model research component image of the institution of higher education to include such units as the theoretical and methodological basis of research image stages of research psychodiagnostic block techniques and components forming the image of higher education institution.